2017
DOI: 10.1155/2017/4675401
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Personality on Online Game Flow Experience and the Eye Blink Rate as an Objective Indicator

Abstract: This study aimed to explore the effects of dominant and compliant personalities, on both flow experience and the external characteristics of flow experience. A total of 48 participants were recruited to play an online game and subsequently asked to recall the songs they had heard while they were playing the game. Eye blink rate was recorded. The results demonstrated that (1) the participant was immersed in the game more if he/she was relatively dominant or noncompliant; (2) the perceptions about the external e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For individual flow – i.e., for those team flow characteristics that are shared with individual flow – there are already elaborated concepts and studies on its physiological correlates (for an overview see Tozman and Peifer, 2016 ; Peifer and Tan, 2021 ) and their potential use for machine learning ( Peifer et al, 2020a ; Rissler et al, 2020 ). Studies show that individual flow experience is for example associated with heart rate variability ( Peifer et al, 2014 ), electrodermal activity ( de Manzano et al, 2010 ), respiration ( de Manzano et al, 2010 ), blinking rate ( Rau et al, 2017 ; Peifer et al, 2019a ), or facial muscle activation ( Kivikangas, 2006 ; de Manzano et al, 2010 ; Nacke and Lindley, 2010 ). Those indicators can be sorted according to the components of flow, i.e., if they relate to absorption, perceived demand-skill balance and/or enjoyment.…”
Section: Complementing a Team Flow Measure By Means Of Collective Communicationmentioning
confidence: 99%
“…For individual flow – i.e., for those team flow characteristics that are shared with individual flow – there are already elaborated concepts and studies on its physiological correlates (for an overview see Tozman and Peifer, 2016 ; Peifer and Tan, 2021 ) and their potential use for machine learning ( Peifer et al, 2020a ; Rissler et al, 2020 ). Studies show that individual flow experience is for example associated with heart rate variability ( Peifer et al, 2014 ), electrodermal activity ( de Manzano et al, 2010 ), respiration ( de Manzano et al, 2010 ), blinking rate ( Rau et al, 2017 ; Peifer et al, 2019a ), or facial muscle activation ( Kivikangas, 2006 ; de Manzano et al, 2010 ; Nacke and Lindley, 2010 ). Those indicators can be sorted according to the components of flow, i.e., if they relate to absorption, perceived demand-skill balance and/or enjoyment.…”
Section: Complementing a Team Flow Measure By Means Of Collective Communicationmentioning
confidence: 99%
“…When playing online games, players need strong concentration and visual attention so that the frequency of blinking eyes decreases. [8] The study conducted by Lee et al [9] found that the frequency of blinking before playing games was 16.24 times per minute and decreased to 8.27 and 9.51 times per minute after one hour and four hours of playing games.…”
Section: Introductionmentioning
confidence: 99%
“…https://e-journal.unair.ac.id/VSEHJ Reduced blinking frequency when playing online games can cause symptoms DED. [3], [8] This DED problem can reduce the quality of life and work productivity by 4% to 19%. [1], [3], [10] A global epidemiological study conducted by dry eye workshop (DEWS) [11] in 2017, the prevalence of DED reached 5 to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is little knowledge of whether and how the effectiveness of these strategies vary across multiple application domains for people of distinct personality traits. Personality has been found to have a significant impact in many areas of Human–Computer Interaction (HCI) including persuasive systems (Sofia et al 2016 ), games (Rau et al 2017 ), gamified systems (Ghaban and Hendley 2019 ), and graphical user interfaces design(Sarsam and Al-Samarraie 2018 ). While there has been research on the impact of personality on the effectiveness of persuasive strategies (Halko and Kientz 2010 ; Hirsh et al 2012 ; Orji et al 2017d ), none has investigated the combined effect of user-dependent factors (personality types) and usage context-dependent factors (different application domains) to establish the generalizability of the strategies or not and develop guidelines for tailoring persuasive gamified systems that takes both the target user personality and application domains into account.…”
Section: Introductionmentioning
confidence: 99%
“…Of all these models, the FFM is the most popular and widely accepted personality model and has been predominantly used in HCI and persuasive technology research. It has been shown that personality factors affect many aspects of HCI including the area of persuasive technology (Alkiş and Taşkaya Temizel 2015 ; Orji et al 2017d ), games (Rau et al 2017 ), gamified systems (Ghaban and Hendley 2019 ), and how people interact with Graphical User Interfaces (Sarsam and Al-Samarraie 2018 ). For example, Orji et al ( 2017d ) investigated how different personality types respond to various persuasive systems used in a persuasive game for alcohol cessation using the FFM.…”
Section: Introductionmentioning
confidence: 99%